2012
DOI: 10.1016/j.cell.2012.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Fruitless Recruits Two Antagonistic Chromatin Factors to Establish Single-Neuron Sexual Dimorphism

Abstract: The Drosophila fruitless (fru) gene encodes a set of putative transcription factors that promote male sexual behavior by controlling the development of sexually dimorphic neuronal circuitry. However, the mechanism whereby fru establishes the sexual fate of neurons remains enigmatic. Here, we show that Fru forms a complex with the transcriptional cofactor Bonus (Bon), which, in turn, recruits either of two chromatin regulators, Histone deacetylase 1 (HDAC1), which masculinizes individual sexually dimorphic neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
131
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(134 citation statements)
references
References 45 publications
(49 reference statements)
3
131
0
Order By: Relevance
“…In this attempt, we found that a null mutation in the bon gene suppresses the phenotypic effects of fru overexpression in the eye. 10,11 In our subsequent analysis, a bon null mutation was shown to exacerbate courtship behavior defects observed in male flies of fru hypomorphic mutants (fru 2 /fru sat ).…”
Section: Bon-dependent Association Of Fru With Two Chromatin Factorsmentioning
confidence: 91%
See 3 more Smart Citations
“…In this attempt, we found that a null mutation in the bon gene suppresses the phenotypic effects of fru overexpression in the eye. 10,11 In our subsequent analysis, a bon null mutation was shown to exacerbate courtship behavior defects observed in male flies of fru hypomorphic mutants (fru 2 /fru sat ).…”
Section: Bon-dependent Association Of Fru With Two Chromatin Factorsmentioning
confidence: 91%
“…12,13 Our immunoprecipitation assays with Drosophila head extracts or S2 cell lysates showed that Bon mediates associations of Fru with HDAC1 or HP1a, which compete with each other for Bon. 11 Moreover, polytene chromosome immunostaining revealed that HDAC1 and HP1a colocalize with Fru at a number of Fru-binding chromosomal sites in a Bon-dependent manner.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Fru M appears to function in a complex with the transcription cofactor Bonus and either histone deacetylase 1 or heterochromatin protein 1a (14). Recent genome-wide screens of RNA expression levels or Fru M binding activity have identified potential Fru M targets, but have lacked independent confirmation of such regulation (15)(16)(17).…”
mentioning
confidence: 99%